Two different pairs of negative integers, x and y, that make the statement x − y = −1 true

Answers

Answer 1
Answer: one way is
solve for x
add y to both sides
x=y-1

sub negative values for y and get negative values for x
if y=-1, x=-2
if y=-3, x=-4
and so on

some points
(-2,-1)
(-3,-2)
(-4,-3)
(-5,-4)
(-6,-5)
etc
Answer 2
Answer: No, X+Y (both of them being negative integers) equal -1. Just a small miscalculation.

Related Questions

A regular polygon could not have an interior angle measure of A. 45º B. 90º C. 150º D. 160º
1.43 x (-19/37) please answer.....
F(13) = -3x+ 7 What’s the answer?
Lane is 10 times Mel's age. If the difference in their age is 27, how old is Mel?
An average Asian elephant weighs about 8,800 pounds. How many tons and pounds is this? a 4 tons 800 pounds b 5 tons 1,200 pounds c 8 tons 200 pounds d 10 tons 200 pounds

What is the solution set of {x | x < -3} ∪ {x | x > 5}

Answers

The union of two sets is defined as all elements that are members of both sets.

The first set evaluuates to (...,...,...-7,-6,-5,-4) and the second eveluates to (6,7,8,9,...,...).

There are no elements that belong to both sets so the solution is the empty set. {∅}

Another way is to think about it in words: "What number(s) are less than -3 and also greater than 5?" There are no numbers that fit both of these.

This math my life depends on it

Answers

A geometric sequence is one in which consecutive terms form a fixed ratio r. In other words, if aₙ is the nth term in the sequence, then

a_n = a_(n-1)r

For example, if a₁ = a is the 1st term, then

2nd term = a₂ = a₁r

3rd term = a₃ = a₂r = a₁r²

4th term = a₄ = a₃r = a₁r³

and so on. It's fairly easy to infer that

nth term = a_n = a_(n-1)r = a_(n-2)r^2 = a_(n-3)r^3 = \cdots = a_1r^(n-1)

14. We're given the 2nd and 5th terms, a₂ = -243 and a₅ = -9, and we use them to find the ratio r.

a₅ = a₄r = a₃r² = a₂r³

-9 = -243 r³

r³ = 1/27

⇒   r = 1/3

Then the 1st term is

a₁ = a₂/r = -243/(1/3) = -729

and the nth term is recursively given by

a_n = \frac13a_(n-1)

and explicitly by

a_n = \left(\frac13\right)^(n-1) a_1 = -(729)/(3^(n-1)) = -(3^6)/(3^(n-1)) = -3^(7-n)

15. Now we have a₄ = 1/72 and a₃ = -1/12. Using what we know about geometric sequences, we have

a₄ / a₃ = (a₃r) / a₃ = r

so that

r = (1/72) / (-1/12) = -1/6

Then the 1st term is

a₁ = a₂/r = a₃/r² = (-1/12) / (-1/6)² = -3

and the nth term is recursively given by

a_n = -\frac16a_(n-1)

and explicitly by

a_n = \left(-\frac16\right)^(n-1) (-3) = -3\cdot(-6)^(1-n) = 3\cdot(-1)^n\cdot6^(1-n)

A is the point with coordinates (4,6)b is the point with coordinates (d,21)
the graident of line AB is 3
what is the value of d

Answers

Answer:

d = 9

Step-by-step explanation:

Calculate the slope of ab then equate to 3.

Calculate the slope m using the slope formula

m = (y_(2)-y_(1)  )/(x_(2)-x_(1)  )

with (x₁, y₁ ) = (4, 6) and (x₂, y₂ ) = (d, 21)

m = (21-6)/(d-4) = (15)/(d-4) = 3 ( multiply both sides by d - 4 )

3(d - 4) = 15 ( divide both sides by 3 )

d - 4 = 5 ( add 4 to both sides )

d = 9

Jackie's broker charges her a commission of $8.25 per ten of stocks she buys or sells. If Jackie buys 69 shares of Alesia Insurance at $10.34 per share, how much will Jackie spend in commission?

Answers

69 = (6 × 10) + 9

6 × $8.25 = $49.50

Jackie will spend $49.50 in commission.

Solve - 2x - 8> 3x + 12.
Please help!

Answers

Answer:

B. X < -4

Step-by-step explanation:

-2x - 8 > 3x + 12

Subtract 3x from both sides

-5x -8 > 12

Add 8 both sides

-5x > 20

Divide -5 both sides

X < -4

Answer: x < -4

Step-by-step explanation:

Subtract 3x from both sides

-5x - 8 > 12

Add 8 to both sides

-5x > 20

Divide both sides by -5

x < -4

Find the vertex of a function f(x)=-3x^2+9x-15 by completing the square

Answers

The vertex will be (3/2, - 33/4)